Maqasid-based Perspective and Its Impact on Directing Laws of Jurisprudence on Family by Malikite School | النظر المقاصــدي عند المــالكية وأثــره في ترشيد فقه الأســرة - Abdul Aziz Wasfi (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2020)
This research examines the concept of Islamic law and its treatment of the subject of the family in terms of its importance as the first cell in the building of society, as well as the statement of its rights, its sound foundations and its strong pillars that guarantee its stability and preserve its existence and durability.One of these pillars is its system of rights, which is the safety valve for its preservation and stability, to ensure its proper use and to avoid any abuse in the light of the fact that Western culture and its intellectual payload promote a declaration of war on the Islamic family rights system as overriding rights Was a cause of the injustice inflicted on women, it is no longer valid for our living reality.The researchers chose the issue of letting the wife to prepare herself for the beginning of a stable family life as a model of study based on the legal texts, fiqh, fatwas of scholars and family calamities in the subject.